Warming rate could influence the thermal resistance in freshwater phytoplankton - Sánchez de Pedro Crespo, Raquel; Melero-Jiménez, Ignacio José; Reul, Andreas; Viruel, María Ángeles; Bañares-España, Elena; Flores-Moya, Antonio; García-Sánchez, María Jesús; Melero-Jiménez, Ignacio José (My University, 2024)
Global warming is altering the composition of freshwater phytoplankton communities due to the differential potential of species to respond to increasing temperatures. Eco-evolutionary theory supports that the rate of environmental deterioration modulates the probability to evolve under selective pressures [1]. Thus, might different warming rates differentially increase the limits of thermal resistance in freshwater phytoplankton? We compared the growth response of one strain of the bloom forming cyanobacterium Microcystis aeruginosa (Kützing) Kützing and the green microalga Chlamydomonas reinhardtii P. A. Dang under two different warming scenarios. We applied a ratchet protocol [2] to test if different warming rates (slow, +2 ºC, and rapid, +4 ºC) could influence the ability of both species to surpass their initial limit of thermal resistance (LTR). After 5 months (128 generations for both species), one of the four populations of M. aeruginosa exposed to slow warming was able to exceed its initial LTR (33 ºC) after 46 generations, being able to grow at 35 ºC, but showing a lower photosynthetic performance than their ancestral populations at control conditions (25ºC). However, at rapid warming none of the M. aeruginosa populations surpassed the initial LTR, as observed in C. reinhardtii regardless of warming rate. Nevertheless, the derived populations of C. reinhardtii showed higher photosynthetic capacity at their initial LTR (37 ºC) compared to the ancestral populations. The ability of natural phytoplankton populations to survive at increasing warming would depend on the species and would be favored by slow temperature increase, at the expense of a physiological cost.
Keywords: Plantas - Efectos del calentamiento global - Congresos; PAM fluorometry; Experimental evolution; Phytoplankton; Global warming; Temperature; Ratchet; Photosynthesis